Submerged hollow fibre membrane fouling : characterization and control - Ebrahim Akhondi (2014)
The filtration behavior and energy consumption of submerged hollow fibre membranes has been investigated in a dead end mode under constant flux operation with periodic backwash. Various operating parameters such as filtration flux, feed concentration, backwash duration, backwash strength, and the aid of air scouring during backwash were investigated to optimize the filtration performance and energy consumption. The results showed that filtration flux and feed concentration have significant effects on membrane fouling rate. In order to maximize the net permeate volume, filtration flux, backwash duration and backwash strength were found to be the most important parameters, which must be carefully selected. To minimize the specific energy consumption, filtration flux, backwash duration and aeration rate during backwash were the most important factors. Experimental results in this study show that the effectiveness of fixed backwash cycles can decrease over time and reach a point at which the backwash effectiveness suddenly decreases. Evidence from transmembrane pressure (TMP) monitoring suggests that the sudden decrease in backwash efficiency occurs when the pressure on the permeate side of the membrane at the end of a backwash cycle does not reach the atmospheric pressure maintained on the feed side. The release of dissolved air on the permeate side of the membrane due to the pressure drop across the membrane was recognized as a major reason for reducing the backwash effectiveness. A mathematical model has been developed to calculate the minimum backwash duration required to reverse the flow through the membrane by increasing the permeate-side pressure up to atmospheric pressure. The minimum required backwash duration depends on the pressure at the beginning of the backwash, backwash flowrate, the amount of air on the permeate side, membrane surface area, water viscosity, temperature, and the membrane and fouling resistance. Adaptation of evapoporometry (EP) for characterization of hollow fibres involving development of the analysis method and also designing and applying a suitable test cell and protocol has been completed. Evapoporometry was used to characterize two different types of UF hollow fibre membrane (PVDF & PAN). The results indicated that evapoporometry was able to adequately characterize pore-size distribution of clean and fouled hollow fibre membranes. The benefits of EP have been highlighted. The changes in pore size distribution (PSD) of UF hollow fibre membranes due to residual fouling and periodical backwashing of the fibres were investigated. PSD analysis showed that the larger pores were more prone to pore blocking than small pores. However, backwashing was more effective in restoring these larger pores. Flow distribution analysis showed that the largest pores played an important role in membrane permeability. However, high pressure backwashing was found to enlarge the membrane pores in an irreversible way. The implications of this for membrane fouling characterization have been discussed.